Bisabolanoic acid A, a new polychiral sesquiterpene with AChE inhibitory activity from a mangrove-derived fungus Colletotrichum sp. Issue 1 (2nd January 2022) - Li, Kun-Long; Dai, Yu; She, Jiang-Lian; Zeng, Yan-Bo; Dai, Hao-Fu; Ou, Shun-Ling; Zhou, Xue-Feng; Liu, Yong-Hong
Abstract: A new polychiral bisabolane sesquiterpene, bisabolanoic acid A (1 ), was isolated from the mangrove-derived fungus Colletotrichum sp. SCSIO KcB3-2. Its planar structure was identified on the basis of spectroscopic data analysis (HRESIMS, 1D, and 2D NMR), and the absolute configurations of three chiral carbons were determined by experimental and calculated electronic circular dichroism (ECD) and optical rotatory dispersion (ORD), together with Mo2 (OAc)4 -induced ECD methods. Bisabolanoic acid A (1 ) showed moderate inhibitory activity against acetylcholinesterase (AChE) with IC50 value of 2.2 μM, and the in silico molecular docking was also performed. Graphical abstract: UF0001